Informal Employment in Bangladesh - Dalisay S. Maligalig; Sining Cuevas; Aleli Rosario (Asian Development Bank (ADB), 2009)
The paper developed a methodology for classifying workers into formal and informal employment using the 2005 Bangladesh Labor Force Survey (LFS). Although the 2005 LFS was not designed to collect data for this purpose, it included questions that can be used to determine whether workers are engaged in formal or informal employment. However, the process of identifying the combination of questions that could distinguish between formal and informal workers was hampered by data inconsistencies that were probably brought about by limitations in data processing and validation. Because 3 years have already passed since data processing was done, the most workable approach was to determine which workers are under formal employment, and to assume that the remaining workers are engaged informally. Results show that 87.71% of the workers in Bangladesh are under informal employment. The highest concentration of informal workers is found in the rural areas (92%). Workers engaged in informal employment are mostly in agriculture; hunting and forestry; wholesale and retail trade; manufacturing; and transport, storage, and communications sectors. On the other hand, formal workers are primarily employed by the government. Women (91.3%) are most likely to be engaged in informal employment than men (86.6%); and women are generally unpaid family workers and in the private household sector. Workers under formal employment are paid better than those under informal arrangements. For each sector, wage differentials between formal and informal workers are significant. Informal workers are found to have significantly less benefits than those with formal employment, except for free meals and free lodging. In particular, self-employed and unpaid workers comprise a little over 20 million of informal workers, although less than 2 million of them enjoy benefits.
hdl:11540/1806
Keywords: 330; Bangladesh; informal employment; informal sector; gender analysis; wage differentials; Erwerbstätigkeit; Informelle Wirtschaft; Bangladesch